General Equilibrium with a Replenishable Natural Resource: A Comment - Lesourne, Jacques (Review of Economic Studies, 1976)
Journal Article General Equilibrium with a Replenishable Natural Resource: A Comment Get access Jacques Lesourne Jacques Lesourne Conservatoire National des Arts et Métiers Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 3, October 1976, Pages 557–560, https://doi.org/10.2307/2297237 Published: 01 October 1976 Article history Received: 01 June 1975 Accepted: 01 March 1976 Published: 01 October 1976